Thermodynamically stable vesicle formation of biodegradable double mPEG-tailed amphiphiles with sulfonate head group. Issue 54 (2nd September 2020) - Ghosh, Rita; Dey, Joykrishna; Kumar, B. V. N. Phani
Abstract : Spontaneous vesicle formation by biodegradable novel double mPEG-tailed amphiphiles. Abstract : The development of efficient, biodegradable and biocompatible surfactants has become a pressing need because of adverse effects of surface-active compounds on the aquatic environment and human health. Cleavable surfactants containing a labile functional group have the ability to eliminate some of these problems. Consequently, PEGylated amphiphiles have found widespread applications in pharmaceutics, household purposes, and drug delivery. Herein we report synthesis and characterization of two novel amphiphiles which to our knowledge are the first examples of double PEG-tailed amphiphiles with an anionic head group. Considering their chemical structure, they are expected to be biodegradable, biocompatible, milder and less irritant than conventional surfactants. The solution behavior of these newly developed amphiphiles was thoroughly investigated in aqueous buffer (pH 7.0) at 25 °C. The surface activity of the compounds in aqueous buffer was studied by surface tension measurements. The self-assembly properties were investigated by various techniques such as fluorescence and NMR spectroscopy, dynamic light scattering, transmission electron microscopy, atomic force microscopy, and isothermal titration calorimetry. Both molecules were found to be surface active in water and exhibit spontaneous vesicle formation in the absence of any additives at room temperature. As in the cases of conventional surfactants, the self-assembly is driven by the hydrophobic effect. The vesicles produced in aqueous media were shown to encapsulate hydrophobic dyes and exhibit structural transitions upon addition of salts. The sensitivity of the vesicles to change in environments qualifies them for potential use in drug delivery.